Polymorphism in molecular crystals - Bernstein, Joel, 1941-2019 (Oxford University Press, 2020)
"Polymorphism in chemistry is the existence of multiple crystal structures for one substance. The properties of a substance are determined by its composition and by its structure. This book summarizes and brings up to date the current knowledge and understading of polymorphism of molecular crystals"--Publisher's description
Keywords: Polymorphism (Crystallography); Molecular crystals.; elektronické knihy; electronic books